Degrees as nominalized properties: Evidence from differential verbal comparatives in Mandarin Chinese - Luo, Qiongpeng; Xie, Zhiguo (Proceedings of Sinn und Bedeutung, 2019)
Whether degrees should be modeled as simple semantic primitives or ontologically complex entities has been an issue in recent formal semantic research. This article aims to make a contribution to this scholarly enterprise by investigating the Differential Verbal Comparative (DVC) construction in Chinese. DVCs exhibit peculiar properties : (i) obligatory differentials, and (ii) DPs as differentials(e.g., liang ben xiaoshuo ‘two CL novel’). We propose that a degree is the entity correlate of a property that is formed on the basis of a measure, akin to Chierchia-style kind. This new kind of degree, coupled with a difference function-based semantics for comparatives, correctly predicts the behaviors of DVCs which would otherwise remain formally inscrutable. This article’s contributions are twofold: (i) it provides direct support for the degree-as-kind analysis by extending its empirical scope; and (ii) by combining degrees as kinds with a difference function-based semantics, it represents an improvement over the previous degree-as-kind analysis based on linear ordering.